Paint the Bridge: College Student Perceptions of Institutional Response to Racial Bias on Campus - Pallas, Adam (My University, 2020)
A recent increase in racial bias incidents on college campuses have ignited a contemporary conversation about the interplay between free speech on college campuses and an institution’s responsibility to create an inclusive learning environment for all. The purpose of this study is to investigate how college students perceive their institution’s response to a racial bias incident, especially when protecting free speech and promoting an inclusive campus climate are presented as antithetical. I utilized a critical race perspective to conduct a qualitative case study of the events of a racial bias incident at the University of Minnesota – Twin Cities. Eight semi-structured interviews with current University of Minnesota students, coupled with an in-depth analysis of the University using an ecological multidimensional framework for campus climate (Hurtado et al., 2012), revealed findings of how participants contextualize and make meaning of the incidents; how participants understand and value free speech, offensive speech, and hate speech; and how participants recalled and reacted to a statement by the University president almost four years after the statement was issued. Implications for future responses to racial bias incidents are discussed. American public higher education institutions’ commitments to free speech and promoting inclusive campus racial climate are also discussed.
University of Minnesota M.A. thesis. September 2020. Major: Organizational Leadership, Policy, and Development. Advisor: Karen Miksch. 1 computer file (PDF); vii, 87 pages.
Keywords: Campus Racial Climate; Critical Race Theory; Free Speech; Higher Education; Qualitative Case Study